I am my Own Voice: The Analysis of Imagery, Sound and Sense and Self-Culture from EFL Mindful Poetry - Piscayanti, Kadek Sonia (Language Circle: Journal of Language and Literature, 2022)
This research is aimed at looking at poetry as a soul of society. It brings about the representation of selfculture in the poet’s life. It is the representation of mindfulness within the poet’s process of writing. In this specific article, I want to see how poetry can be seen as a soul of poetry from at least three perspectives, firstly from the imagery, secondly from sound and sense and thirdly from the self-culture. The method used in this research is narrative inquiry and the instruments used are interview guide and poetry writing rubrics. The result shows that the poets in this research used imagery, sound and sense and self-culture in their poetry as the voice of their own. At the same time they also feel that their voice matters, as the part of society.